Different approaches under one umbrella: constructing the failure of intercultural education against the obvious - Spajić-Vrkaš, Vedrana (2013)
In many countries the theory of intercultural education is poorly informed by the human rights and active citizenship discourses and still aims to promote respect for the culturally different without questioning, in the one hand, the issues of recognition, participation, self-representation and redistribution as the keys to a sustainable respect and, in the other hand, the principles for restructuring the society to make the respect contextually meaningful. In this way, the psychological dimension remains dominant in educational practice and disconnected from a set of powerful structural determinants of intercultural learning which, in the age of neo-conservative and neo-liberal attacks on educational policies and practices, threatens to distort the role of intercultural education in bringing about societal changes in line with the critical intercultural education approaches. In trying to contribute to understanding of the roots of this reduction, we shall, in this key-note presentation, offer an approach in which different conceptualisations of intercultural education are related to the four distinctive eras. The delineation of these eras seems important in understanding what conceptual and strategic tools the Western societies have used to accommodate to the different, as well as how and why these tools have changed, especially in reference to education. Drawing from that, we shall argue in conclusion that an unproblematic categorisation of the context-free approaches lacking the dimensions of human rights and active citizenship as “multicultural” or “intercultural education” is a means of constructing a neo-romanticised version of intercultural education for the purpose of its failure.
ENG